'Am I sexually abused?' Consent in a coach-athlete lesbian relationship. Issue 4 (4th May 2018) - Johansson, Susanne
ABSTRACT: Elite-athlete Karin was 17 years old when the considerably older team coach Selma became her girlfriend. Responding to calls to prevent harm and sexual abuse in sport, this study represents Karin's story, investigates how she makes sense of her coach–athlete sexual relationship, and analyses what can be learnt about consent. Although sexual consent is often the defining criterion of sexual abuse, consent is rarely explicitly defined or its social implications examined. Moreover, there are no studies on coach–athlete lesbian or gay relationships despite sexual minority vulnerability. The interview with Karin was analysed using narrative case study methods; represented as a short story and discussed in reference to sexual consent theory. The analysis outlines contextual factors conditioning the negotiation of consent and problematises heteronormative, gendered perpetrator and victim stereotypes. Secrecy, alienation and isolation is recognised, extending into additional vulnerability inflicted on socially problematic and atypical coach–athlete relationships. In conclusion, social implications of consent are more complex than yes/no to sex or inherent incapability to consent. Consent is multi-layered, alternately absent and present; an ongoing process that includes compromises, contradictions and (re)negotiations influenced by structure and agency. Further research examining a diversity of sexual experiences among majorities and minorities is proposed.